GHG emissions from China's international sea freight transport: a review and the future trend. (2018) - To, W.M.; Lee, Peter K.C.
This paper reviews the development of China's international sea freight throughput during the period 1980-2015 and uses logistic model to estimate the future growth of international sea freight and the associated increase in the emission of greenhouse gases (GHG). The review showed that China's international sea freight throughput increased from 353.2 billion ton-km in 1980 to 5423.6 billion ton-km in 2015. Meanwhile China's international container throughput increased from 64.3 thousand 20-foot equivalent units (TEU) to 189 million TEU (over 27% of the world's container traffic flow) in 2015. The associated GHG emission increased from 2.60 million tons CO2 -eq in 1980 to 39.95 million tons CO2 -eq in 2015. Although the logistic growth model indicated that China's international sea freight and container throughputs reached maximum growth rates in 2008, GHG emissions due to China's international sea freight would continuously increase to over 53 million tons in 2020.